Satire vor Gericht Eine Auseinandersetzung mit den Politsatire-Plakaten Klaus Staecks aus rechtlicher und kunsthistorischer Perspektive - Brinkmann, Franziska (Bild und Recht - Studien zur Regulierung des Visuellen, 2021)
"Deutsche Arbeiter! Die SPD will euch eure Villen im Tessin wegnehmen" In his posters, the artist and lawyer Klaus Staeck commented on the political events of the late FRG. He continues to confront his audience with major social issues such as gender equality, climate protection, and peace policy - to the particular annoyance of those affected. In the numerous legal proceedings brought against him, the tensions of satirical expression between artistic freedom and freedom of opinion, as well as the personal rights of those affected, become clear. Access to Staeck's archive made it possible to conduct a comprehensive study of his posters and associated legal proceedings from the perspectives of art history and law.